THE INFLUENCE OF UNDERSTANDING ISLAMIC RELIGIOUS EDUCATION ON STUDENTS LEARNING MOTIVATION AT SMK PONCOL 65 CENTRAL JAKARTA - Fathnur, Dody Ahmad; Nahuda, Nahuda (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study aims to analyze the influence of understanding Islamic Religious Education on students' learning motivation at SMK Poncol 65 East Jakarta. It uses a quantitative descriptive method with statistical data analysis techniques to test the relationship between understanding Islamic Religious Education and students' learning motivation. The research sample consists of students who were selected randomly. Data were collected using a questionnaire that had been tested for validity and reliability. The study's results showed that understanding Islamic Religious Education had a magnitude of 0.699 on students' learning motivation. Based on statistical tests, the correlation value obtained (ro) of 0.699 was more significant than the rt value at a significance level of 5% (0.291) and 1% (0.376). Thus, the null hypothesis is rejected, and the alternative hypothesis is accepted, indicating a significant influence between understanding Islamic Religious Education and students' learning motivation. This study concludes that understanding Islamic Religious Education can increase students' learning motivation. For students who receive less attention from their parents, learning motivation can be increased by providing more fantastic encouragement at school. Educators are expected to motivate students in various ways, such as by offering rewards or awards that can motivate them enthusiastically.